STRATEGI BADAN PENDAPATAN DAERAH PROVINSI RIAU DALAM MEMBANGUN KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Nurfadila Nurfadila; Khairul Amri (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Tax is a people's contribution to the state treasury which has been determined directly by law to surrender part of the wealth owned. The Regional Revenue Agency of Riau Province has goals and objectives, namely the Realization of Regional Original Revenue as the main supporter of the smooth running of the administration of the Riau Province Government, the target of which is Increasing Regional Revenue. The Raiu Provincial Bapenda issued a PAD Management Program and outreach activities on Innovations that were issued to facilitate and improve motor vehicle taxpayer compliance in the city of Pekanbaru by issuing innovations. The purpose of this study was to determine the strategy of the Regional Revenue Agency of Riau Province in Building Motor Vehicle Taxpayer Compliance in the city of Pekanbaru. The type of research used in this research is descriptive qualitative. The required data collection is both primary and secondary data from interviews, observations, documentation, and then analyzed so that conclusions can be drawn from the research problem. The programs and activities planned in accordance with the strategic plan in the process of issuing innovations have not run smoothly, while the obstacles to this issued innovation are the lack of supporting apparatus which makes this innovation not run as smoothly as it should, the Riau Provincial Revenue Agency has not increased from the supporting apparatus that supporting the smooth running of every policy that is made, as well as the lack of public trust in the government is an obstacle for the Riau Province Bapenda to gain public awareness.